Synergistic effects of turmeric, banana peels, and onion extracts on broiler performance, mechanical properties, microbial quality, and chicken meat quality assessment - Ahmed M. Abdulfattah; Ahmed M. Abdulfattah; Fayez Alsulaimani; Fayez Alsulaimani; Ahmed M. Basri; Ahmed M. Basri; Nashi K. Alqahtani; Hilary Uguru; Okeoghene Eboibi; D. E. Edafiadhe; Rokayya Sami; Mahmoud Helal (Frontiers in Sustainable Food Systems)
This study investigated the effects of turmeric extract (TE), banana peel extract (PE), and onion extract (OE) on the physiological health status and meat quality of broilers. Two-week-old “Cobb 500” chicks were divided into seven treatment groups: the control (distilled water), T1 (100 mL of TE), T2 (100 mL of PE), T3 (100 mL of OE), T4 (100 mL of TE + 100 mL of PE), T5 (100 mL of TE + 100 mL of OE), and T6 (100 mL of PE + 100 mL of OE). Each treatment solution (100 mL or 200 mL, as applicable) was diluted in 4 L of water and administered to the birds in their drinking water three times a week throughout the experiment. After the 8-week experimental period, the birds’ body weight gain, protein content, water-holding capacity, total lipid content, microbial loads, and the mechanical properties of boiler offal were assessed using standard techniques. The results showed that all supplements had significant effects on all the parameters investigated (p ≤ 0.05). The bodyweight gains for the control and treatments T1 through T6 were 1.87, 2.20, 2.03, 2.12, 2.34, 2.42, and 2.26 kg, respectively. Additionally, the extracts substantially reduced the lipid content in broiler meat while enhancing water-holding capacity (WHC), protein content, packed cell volume (PCV), red blood cell (RBC) count, and white blood cell (WBC) count, antimicrobial activity, and shear force. Moreover, the data revealed that the hybridized additive treatment yielded better results compared to single-extract treatments. These findings hold promising implications for the livestock industry, particularly in promoting sustainable growth, enhancing animal performance, and improving meat quality.